ANALISIS PENGENDALIAN KUALITAS MELALUI EVALUASI DAN PERBAIKAN PROSES PRODUKSI DENGAN PENDEKATAN METODE CONTROL CHART DAN METODE TAGUCHI - Susetyo, Joko; Yusuf, Muhammad; Saputro, Ardi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
Quality is the most important thing in business to get more consumers. Quality will be better if those kinds of processes produced with good constancy. Research was held in Coca Cola Bottling Company Indonesia, problems which were emerging are the sweet disposal (ºBrix) from the product is unstable. Control Chart Method is used to get the condition of production process which is moving, than improvement will be done through Taguchi Method approach. Improvement start from election of factors which influence for those quality’s characteristic as well as level value, and than will be basic for the Orthogonal Array election. Result of analysis is processed through noise signal to ratio (SNR) and Analysis of Variance. Based on research, it was got result that is the best setting level for control factor which is influenced to stability sweet disposal value (ºBrix) are first setting of sweetness disposal simple syrup is 59 ºBrix, addition of concentrate is 1.25 units, and water disposal is 80 %. Quality is the most important thing in business to get more consumers. Quality will be better if those kinds of processes produced with good constancy. Research was held in Coca Cola Bottling Company Indonesia, problems which were emerging are the sweet disposal (ºBrix) from the product is unstable. Control Chart Method is used to get the condition of production process which is moving, than improvement will be done through Taguchi Method approach. Improvement start from election of factors which influence for those quality’s characteristic as well as level value, and than will be basic for the Orthogonal Array election. Result of analysis is processed through noise signal to ratio (SNR) and Analysis of Variance. Based on research, it was got result that is the best setting level for control factor which is influenced to stability sweet disposal value (ºBrix) are first setting of sweetness disposal simple syrup is 59 ºBrix, addition of concentrate is 1.25 units, and water disposal is 80 %.